Особливості організації та ведення бухгалтерського обліку на підприємствах України - Лошакова, Світлана Євгенівна (НТУ "ХПІ", 2018)
Розглядаються проблеми реформування системи бухгалтерського обліку та фінансової звітності на підприємствах України. Визначено необхідність обґрунтованого підходу до формування облікової політики, складання наказу про облікову політику. Проведено порівняння застосування різних форм ведення та організації бухгалтерського обліку для підприємств. Пропонується враховувати можливості та обмеження застосування форм ведення та організації бухгалтерського обліку для конкретного підприємства з метою підвищення ефективності та зменшення витрат підприємства на ведення обліку.

The problems of reforming the accounting and financial reporting system at Ukrainian enterprises are considered. The study of modern approaches to accounting in enterprises of different organizational and legal forms of ownership, effective system of accounting in enterprises, and determination of peculiarities of implementation in accounting companies, taking into account which will provide an opportunity to ensure effective organization of accounting in the enterprise. The necessity of a reasonable approach to formation of accounting policy, drawing up an order on accounting policy are determined. A comparison of the application of various forms of management and organization of accounti ng for enterprises, such as independent accounting and reporting directly by the owner or manager of the enterprise, the introduction of the position of an accountant in the state of the enterprise or the creation of an accounting department headed by a chief accountant, the use of services of a specialist in accounting, registered as an entrepreneur without the creation of a legal entity, on a contractual basis accounting a registered accounting or audit firm are investigated. It is proposed to take into account the possibilities and limitations of the use of forms of management and organization of accounting for a particular enterprise in order to increase the efficiency and reduce the costs of the enterprise for accounting.
Features of organizing and conducting of accounting at Ukrainian enterprises
Keywords: облікова політика; форми ведення; аутсорсинг; ефективність; accounting; accounting policy; forms of accounting; organization of accounting; outsourcing; efficiency